scRNA-seq characterizing the heterogeneity of fibroblasts in breast cancer reveals a novel subtype SFRP4+ CAF that inhibits migration and predicts prognosis - Ning, Lvwen; Quan, Chuntao; Wang, Yue; Wu, Zhijie; Yuan, Peixiu; Xie, Ni (Frontiers in Oncology, 2024)
Cancer-associated fibroblasts (CAFs) are a heterogeneous population of cells that influence the tumor microenvironment and the response to therapy in breast cancer (BC). Eight CAF subtypes were identified from single-cell RNA sequencing (scRNA-seq) in five tumor and six adjacent normal tissues. One of these subtypes, SFRP4+ CAFs, was novel and more prevalent in normal tissues. The existence of SFRP4+ CAFs were confirmed in two independent scRNA-seq datasets and a spatial transcriptomics dataset. We found that SFRP4+ CAFs inhibited BC cell migration and epithelial-mesenchymal transition (EMT) by secreting SFRP4 and modulating the WNT pathway. We also demonstrated that higher expression of SFRP4+ CAF markers was associated with better survival and treatment response in BC patients. Our study characterized the heterogeneity of CAFs in BC and showed a new SFRP4+ CAF subtype that suppresses BC migration, providing a potential biomarker for precision prognosis and therapy.